Detecting sound waves generated by leaks in buried water distribution pipes - Kirby, Ray; Duan, Wenbo; Karimi, Mahmoud; Brennan, Michael [UNESP]; Kessissoglou, Nicole (My University, 2017)
It is common to use guided sound waves to detect leaks or cracks in pipelines. Applications include the nondestructive testing of oil and gas pipelines, which normally takes places at ultrasonic frequencies, as well as the detection of leaks and ruptures in water filled pipes at much lower audio frequencies. However, if the pipe is buried then sound leaks out of the pipe into the surrounding medium and this lowers the acoustic energy travelling along the pipe wall. This has the potential to limit the applications of this technology, and so it is necessary to develop knowledge of the acoustic properties of the guided waves in order to optimise detection techniques. Accordingly, this work examines the properties of sound waves propagating in an infinitely long fluid-filled buried pipe, with application to leak detection at low audio frequencies. A parametric study is undertaken to examine the sensitivity of sound propagation to the properties of the internal liquid, pipe walls and of the surrounding medium.